Lumbar tinea versicolor and spinal anaesthesia - Mohd Zulfakar Mazlan (IDCases, 2019)
Infection to the meningeal layer causing meningitis is one of the most feared complications of spinal anaesthesia. Anaesthetists will avoid spinal anaesthesia for those who are having skin infection at the puncture site. However in obstetric population, anaesthetist will try their best to avoid general anaesthesia due to its unwanted effects and complications. Strict and appropriate antiseptic measures such as chlorhexidine 0.5% with 70% alcohol has been suggested to reduce risk of transmission of microorganisms into subarachnoid space. We reported a parturient who had generalized tinea versicolor at the lumbar area, safely anaesthetized under spinal anaesthesia through meticulous antiseptic skin preparation who required delivery by caesarean section. Keywords: Tinea versicolor, Spinal anaesthesia, Caesarean section